Empowering Human Capital Through Islamic Microfinance: A Pathway to Achieving SDGs in Indonesia - Alifa, Nabiela Rizki; Amani, Akbar Riskal; Zuhri, Arif Rachman; Chng, Norlila Binti Amin (Indonesian Journal of Economics and Management, 2025)
This study examines how Islamic microfinance contributes to the Sustainable Development Goals (SDGs) in Indonesia, focusing on BTPN Syariah’s Mekaar program. A qualitative approach was employed, combining thematic analysis with sentiment analytics using Python-based natural language processing (NLP). Data were derived from beneficiary statements, categorized into ten impact areas including poverty alleviation, education, health, empowerment, and sharia values. The results show that the program positively influences SDG 1 (No Poverty), SDG 4 (Quality Education), SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), SDG 10 (Reduced Inequalities), and SDG 16 (Peace, Justice, and Strong Institutions). Beneficiaries experienced increased income, improved access to basic services, enhanced financial literacy, and empowerment through sharia-compliant and value-driven financing. Sentiment analysis revealed a predominance of neutral and positive responses, with particularly strong positivity in categories related to spiritual comfort, ethical business practices, and social solidarity. This study concludes that Islamic microfinance, when implemented through a structured, ethical, and mentoring-supported model, functions not only as a financial instrument but also as a strategic development tool aligned with global sustainability goals.